Asymmetric Alkynylation of β‐Ketoesters and Naphthols Promoted by New Chiral Biphenylic Iodanes. Issue 54 (21st August 2017) - Companys, Simon; Peixoto, Philippe A.; Bosset, Cyril; Chassaing, Stefan; Miqueu, Karinne; Sotiropoulos, Jean‐Marc; Pouységu, Laurent; Quideau, Stéphane
Abstract: The preparation of new chiral biphenylic λ 3 ‐iodane reagents bearing transferable alkynyl ligands is described. These reagents transfer their carbon‐based ligands onto β‐ketoesters with an enantiomeric excess ( ee ) up to 68 %, and most remarkably, enable the dearomative alkynylation of naphthols in good to high yields up to 84 %  ee . Abstract : The preparation of new axially chiral biphenylic iodine(III) reagents equipped with alkynyl ligands is described. These bis(λ 3 ‐iodane) reagents demonstrate their capacity to promote the asymmetric alkynylation of β‐ketoesters with enantiomeric excesses up to 68 %, and most remarkably, to enable the dearomative alkynylation of naphthols with enantiomeric excesses up to 84 %.